2014
DOI: 10.1073/pnas.1412608111
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA profiles in human patients with acetaminophen hepatotoxicity or ischemic hepatitis

Abstract: We have identified, by quantitative real-time PCR, hundreds of miRNAs that are dramatically elevated in the plasma or serum of acetaminophen (APAP) overdose patients. Most of these circulating microRNAs decrease toward normal levels during treatment with N-acetyl cysteine (NAC). We identified a set of 11 miRNAs whose profiles and dynamics in the circulation during NAC treatment can discriminate APAP hepatotoxicity from ischemic hepatitis. The elevation of certain miRNAs can precede the dramatic rise in the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 28 publications
8
169
0
1
Order By: Relevance
“…Bioinformatic analysis predicted that more than 60% of human genes are targets of miRNAs [4]. Moreover, the accumulated evidence has demonstrated that over 100 circulating miRNAs can be detected in healthy individuals [5]. Although the exact origins and biological functions of circulating miRNAs are still unclear, many studies revealed that circulating miRNAs could be markers of disease progression, prognosis, or diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis predicted that more than 60% of human genes are targets of miRNAs [4]. Moreover, the accumulated evidence has demonstrated that over 100 circulating miRNAs can be detected in healthy individuals [5]. Although the exact origins and biological functions of circulating miRNAs are still unclear, many studies revealed that circulating miRNAs could be markers of disease progression, prognosis, or diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced sensitivity is not only reflected in an earlier increase in the plasma levels of these biomarkers but also in a more rapid decline [248, 252], which makes most of these compounds more accurate indicators of the time course of acute cell death compared to ALT and AST [253]. Another use of biomarkers such as plasma miRNA profiles can be used to distinguish between clinical conditions that are very similar such as acute liver injury after an APAP overdose and hypoxic hepatitis [257]. However, the clinical application of these parameters is currently limited as the time to obtain the information is generally too long to impact patient treatment.…”
Section: Mitochondrial Biomarkers In Drug-induced Liver Injurymentioning
confidence: 99%
“…Recent advances demonstrate the use of miRNAs as sensitive diagnostic and prognostic biomarkers for liver injury 35 , but less progress has been made in exploiting therapeutically novel genes and pathways or circulating metabolites with contributing roles in preventing/mitigating acute liver injury. Thus, identifying key signaling molecules or catalytic products of FMO3 mediating cellular differentiation has much therapeutic usefulness.…”
Section: Gene Expression and Proteome Profiling In Autoprotection/hetmentioning
confidence: 99%